UPAYA MENINGKATKAN PEMBELAJARAN RENANG MELALUI PENDEKATAN WATER FUN GAMES PADA SISWA KELAS IV SDN I LELEDE - Putri Aulia Rifli; Lalu Sapta Wijaya K.; Rindawan (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
This research aims to determine the improvement of learnig in swimming, especially in freestyle, through a water fun games approach. This research method uses classroom action research method (CAR). This research was carried out in two cycles, with each cycle consisting of planning, implementing actions, observing and reflecting. The research subject was class IV SDN I Lelede Academic Year, totaling 20 students, 10 male students, 10 female students. Data collection techniques through observation of learning implementation in each cycle and knowledge and attitude tests. Data validity using triangulation techniques to see trends that occur in learning activities. The initial condition before it was carried out (CAR) there were no students who had completed swimming lessons or 0, in cycle I it increased to 13 students, in cycle II it increased to all students. The water fun games approach contributes to increasing swimming learning. The conclusions of this research are as follows: the water fun games approach can improve swimming learning for class IV students at SDN Lelede academic year. The achievement of swimming learning completenes from initial conditions to cycle I was 65%, from cycle II was 35%, the overal increase in learning completeness from initial conditions to cycle II was 100%.